Hand-held, clinical dual mode ultrasound - photoacoustic imaging of rat urinary bladder and its applications - Sivasubramanian, Kathyayini (2018)
Urinary bladder imaging is critical to diagnose urinary tract disorders, and bladder cancer. There is a great need for safe, non-invasive, and sensitive imaging technique which enables bladder imaging. Photoacoustic imaging is a rapidly growing imaging technique for various biological applications. It can be combined with clinical ultrasound imaging system for hand-held, dual modal ultrasound-photoacoustic real-time imaging. Structural (bladder wall) and functional (accretion of nanoparticles) bladder imaging is shown here with combined ultrasound and photoacoustic imaging in rats. Photoacoustic images of bladder wall is shown using black ink as the contrast agent. Chicken tissues were stacked on the abdomen of the animal to demonstrate the feasibility of photoacoustic imaging till a depth of 2 cm. Also, the feasibility of photoacoustic imaging for a common bladder disorder, vesicoureteral reflux is studied using urinary tract mimicking phantom. It is also shown that a clinical ultrasound system can be used for photoacoustic imaging of non-invasive clearance study of gold nanorods from circulation by monitoring the gradual accumulation of the gold nanorods in the bladder. The time taken for accumulation of nanorods in the bladder can be used as an indicator of the clearance rate of the nanoparticle circulation from the body.